Utilzation of industrial waste as a filling material - Sahoo, Sanjeet; Mohanty, Chitta Ranjan; Panda, Harapriya; Dash, Rakesh Ranjan (Recent Research in Science and Technology, 2014)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–> <span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">Iron and Steel have played an important role in the development of human civilization over the recent years. Steel by itself is one of the most environment friendly products used in our daily life. Steel has been a material of choice for innumerable applications all along in the past, and it is likely to continue to be an important material for use in the foreseeable future. The world steel production has been increasing from year to year and has already crossed the 1 billion tonnes mark for the first time in 2004. During the intervening period, steel production has grown very fast, and in 2010, global steel production has exceeded 1.4 billion tonnes. The rapid increas has been led by China accounting for more than 45% of world steel production. China is not only the largest producer of steel (627 million tonnes), it is also the largest consumer of steel (576 million tonnes) followed by the United States and India. Sponge iron is the intermediate stage of steel production. During the process of production of the sponge iron, large amount of solid waste is produced. So it is necessary to manage/reuse the waste in proper ways. Over the last few years, environmental and economical issues have stimulated interest in the development of alternative materials and reuse of industrial waste/by-products that can fulfil the standard specification. Dolochar is such a type of solid waste generated from sponge iron industries. Safe disposal of dolochar waste is a major problem for the earth. It is produced in large quantities due to rapid industrialisation. Dolochar is a black coal like material having crystalline structure; contain SiO2, Al2O3, Fe2O3, CaO, MgO and FC (Fixed carbon). Its major constituent is SiO2. The objective of this paper is to provide a detailed study on the characteristics and effective utilisation of the industrial waste (dolochar). The waste sample was collected form a local sponge iron industry located at Sambalpur and different geotechnical parameters such as Light compaction test (Cu, Cc), Specific gravity test, Unit weight test, pH test, Sieve analysis, direct shear test (cohesion, angle of internal friction) and Chemical analysis have been evaluated to find out its suitability as a filling material. <!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–>